Developing and upgrading creative tourism by creating value through tourism activities in Phuket province - Pattanameteewit, Russarin; Thongkerd, Monsirada (Edelweiss Applied Science and Technology, 2025)
This study explores and advances creative community-based tourism in Phuket, Thailand, using a mixed-methods design. Quantitative data were collected from 385 tourists (sample size via W.G. Cochran’s formula, 95% confidence) using structured questionnaires and analyzed with descriptive statistics and multiple regression. Qualitative insights from in-depth interviews with 17 tourism entrepreneurs and officials were examined through content analysis to contextualize and validate the survey results. Tourists assessed creative tourism across three value dimensions: functional (practical benefits and service utility), social (cultural exchange and interaction), and emotional (enjoyment and meaningful engagement). Local communities deliver experiences in cultural heritage, arts and crafts, everyday lifestyles, media-related activities, and personalized offerings. Key drivers of enhanced experiences include community participation (R² = .553), destination uniqueness and identity (R² = .612), balance of tourist satisfaction and host benefits (R² = .631), sustainability (R² = .334), and the quality of tourist–host relationships (R² = .386). Practical guidelines emphasize safeguarding local identity, deepening community participation, strengthening marketing communication, and promoting long-term cultural and environmental stewardship. The findings offer actionable strategies for policymakers and community leaders to co-create resilient, inclusive models positioning Phuket as a leading creative tourism destination.